Nepotism in organizations - Jones, Robert G., Dr. (New York : Routledge, 2012)
"Preface Nepotism is a pervasive phenomenon in human organizations (Bellow, 2003). The Family Firm Institute (FFI, 2009), a group of practitioners and academics with about 1,500 members, is designed to provide "education and networking services" to consultants of family firms. The Web page for FFI (www.ffi.org) states that family firms are "the dominant form of business organization worldwide." Although this statement appears to be unsubstantiated by research evidence, it would be easy to argue that family connections are a major determinant of behavior in organizations. For example, major stockholders of one of the most successful business enterprises in the last century, Walmart, are relatives of its founder. It is not hard to find other examples of the integration of familial and organizational relationships (Bellow, 2003). Given that a primary purpose of industrial-organizational (I-O) psychology is to study behavior in work organizations from the perspective of scientific psychology, it is remarkable how little descriptive research exists on this topic. A PsychInfo search using the search phrase "nepotism and organizations" yielded 27 articles, and included several about animal behavior (with notable exceptions in the I-O psychology literature by Werbel and Hames, 1996, and Kets de Vries, 1993). Apologists might argue that broader organizational studies have dealt with this under such umbrellas as social capital. However, research in ethological journals suggests that there is a meaningful set of psychological phenomena related specifically to nepotism that has not been explored in organizations. The titles found in this search ("In Praise of Nepotism," "Anti-Nepotism Reconsidered," "Nepotism: Boon or Bane") suggest another possible explanation for this lack of"--
Defining a psychology of nepotism / Robert G. Jones -- Nepotism and employment law / Arthur Gutman -- The nepotistic organization : what is this place and how do the people make it? / Paul M. Muchinsky -- nepotism and career choice, job search, and job choice / Edwin A. J. van Hooft and Tracy Stout -- Nepotism and organizational homogeneity : how the ASA process is accelerated by nonmerit-based decision making / Marcus W. Dickson, Levi R. G. Nieminen, and Benjamin J. Biermeier-Hanson -- Nepotism and the commitment of relevant parties / Thomas E. Becker -- Nepotism practices and the work-family interface / Aline Masuda and Michelle Visio -- Nepotism and leadership / Ketan H. Mhatre, Ronald E. Riggio, and Heidi R. Riggio -- The cultural boundary on managing nepotism / Guillermo Wated and Juan I. Sanchez -- A model of organizational nepotism / Bridgette K. Mulder -- Toward a new understanding of nepotistic organizational behavior / Robert G. Jones.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Family corporations; Nepotism; Electronic books